Application of the Law of Crashing into Deaths of UI Students is an Ordinary Offense in Relation to Restorative Justice - Panggabean, Tardip (Journal of Law, Politic and Humanities, 2023)
The aim of research are to know stop the investigation of Ordinary Delicts/Reports at the Police at the request of the perpetrator and the victim. To know form a mechanism to stop investigations into Ordinary Offenses/Reports based on the concept of restorative justice. This research uses normative law research using normative case studies in the form of legal behavior products, for example reviewing laws. The main subject of the study is law which is conceptualized as a norm or rule that applies in society and becomes a reference for everyone's behavior. The finding of research are Polri investigators are aware that there is a weak point in the use of discretion to stop investigations based on the concept of restorative justice, namely the absence of written rules that serve as a legal basis for investigators. The legal basis should be constructed through several laws and regulations and the ability of Polri investigators as public officials to make decisions based on discretion. The current construction of reasoning departs from the Telegram Bareskrim Polri Number: STR/583/VIII/2012 dated 8 August 2012 and several technical instructions from internal Polri institutions.